Studying Roman Economy and Imperial Food Supply. Conceptual and Historical Premises of the Study of the Economic Initiatives of the Emperors in the 1st and 2nd Century AD - Scapini, Marianna (Gerión. Revista de Historia Antigua, 2016)
This paper is aimed at providing a scrupulous conceptual and historical framework in which to contextualize further investigations concerning the imperial economic initiatives in the first two centuries of the Roman Empire. I will focus mainly on the problem of food supply. Indeed, this theme was at the core of imperial economic concerns and had, to a certain extent, a role within the development of Roman economic channels themselves. I will argue that grain euergetism was able to represent an effective means of positively affecting provincial food supply, given the fact that central control was structurally limited in the territories of the Empire. For this same reason, I also believe that imperial grain beneficia in the provinces represented an actual attempt to increase central control over imperial grain management.
Keywords: Roman economy; Food supply; Annona; Frumentarian euergetism; Centre vs periphery; Market; Redistribution